Insights into professional learning for intensive Block Model: Lessons from a participatory evaluation for capacity building - Samarawickrema , Gayani; Cleary, Kaye; Gauci, Sally (Journal of University Teaching and Learning Practice, 2024)
We share lessons gained through supporting an institution-wide curriculum innovation via a post-graduate professional learning program. At the inception of the innovation, an intensive Block Model (BM) was unfamiliar to both the institution and its professional learning facilitators. The Graduate Certificate of Tertiary Education was re-modelled with BM as the heart of professional learning so academics would encounter BM as students. The program modelled BM principles, reinforced by meta-conversations to provide students with a reflective, immersive experience. Through a participatory evaluation, professional learning facilitators’ individual reflections were distilled to generate collaborative insights into academics’ capacity building for BM. Their lessons inform strategies to cultivate institution-wide capability-building including their own professional growth. Lessons shape the study recommendations. Recommendations originate from effectively engaging time-poor, diverse cohorts. (1) In recognition of the ease with which students can fall behind, embedding strategies to manage their time and stress helps to maintain a realistic study pace. (2) Authentic assessments provide students with useful products for their teaching. (3) Peer-feedback and examples of students’ work exposes them to how their colleagues present their work and illustrates good BM practices. (4) Modelling BM principles must be reinforced by meta-conversations to provide students with a reflective, immersive experience of the pedagogical principals. We observed that well planned efficiencies for students often provide consequent efficiencies for staff. These insights are captured in a model for scalable institutional-based professional learning practice. Capability growth flourishes at the intersection of action, reflection and evaluation. Professional collegial conversations are the catalyst for developing context-relevant professional learning.